Reassessing the influence of teacher role models in student purchasing decisions - Rohmatin, Alfa; Ridwan, Endan Hamdan; Gandara, Tedi; Permana, Diansyah; Masitoh, Imas (Trigin Publisher, 2025)
This study stems from the anomaly of consumer behavior in the pesantren environment, where the exemplary behavior of teachers as a subjective norm is assumed to strongly influence the purchasing decisions of santri, a phenomenon that challenges rational consumer theory. The purpose of this study is to quantitatively test the influence of Subjective Norms (Teacher Exemplarity) on the purchasing decisions of sarong products among santri at Pesantren Al Istiqomah. Using a quantitative approach through a survey, the data were analyzed using simple linear regression techniques. Surprisingly, the statistical analysis results showed no significant influence (Sig. 0.634 > 0.05), with a very low coefficient of determination (R Square) of 0.003. This finding conclusively rejects the research hypothesis, leading to the conclusion that teacher role modeling is not the primary determinant in students' purchasing decisions. The results indicate that within the walls of the boarding school, economic rationality such as considerations of price and product quality is likely to play a far more dominant role than the social impulse to emulate role models.